Law as a system: duty of coherence and antinomies according Norberto Bobbio (Revista da Faculdade de Direito, Universidade de São Paulo, 2012)
The Norberto Bobbio’s theory of the law is based on the pillars of unity, consistency and completeness. Consistency is a trait, complemented by other, that characterizes legal systems. Legal ordinance is considered a legal system. In the solution of the antinomies, the adoption of criteria as objective as possible is an imperative of justice.